2020
DOI: 10.22364/eeb.18.02
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of lactic acid bacteria against Fusarium species responsible for tomato crown and root rots

Abstract: Three lactic acid bacteria (LAB) (Lactobacillus delbruckii subsp. bulgaricus, Leuconostoc mesenteroides subsp. dextranicum and Lactococcus lactis subsp. diacetylactis) were tested for their antagonistic activity to reduce fungal growth of nine isolates of Fusarium species (F. oxysporum, F. redolens and F. solani), agents of tomato crown and root rot, the most destructive disease of tomato (Solanum lycopersicum) in Algeria. The LAB tested significantly inhibited nine strains of Fusarium spp. on Potato dextrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the metabolic profiles of the LAB strains, the most abundant compounds were found to be from organic acids and ethanol. Zebboudj et al (2020) indicated that L. lactis subsp. diacetylactis were able to inhibit Fusarium species of tomato crown and root rot up to 62.42% on MRS agar medium.…”
Section: Defending Plant Against Biotic Stressmentioning
confidence: 99%
“…In the metabolic profiles of the LAB strains, the most abundant compounds were found to be from organic acids and ethanol. Zebboudj et al (2020) indicated that L. lactis subsp. diacetylactis were able to inhibit Fusarium species of tomato crown and root rot up to 62.42% on MRS agar medium.…”
Section: Defending Plant Against Biotic Stressmentioning
confidence: 99%
“…These methods include maintaining good storage conditions, application of chemical and physical treatments [12], including acidic/basic solutions [13], ozonation [14], UV irradiation [15] and adsorption [16], or the application of antagonistic fungal strains, which inhibit unwanted moulds including mycotoxin producers [17]. Various studies showed that lactic acid bacteria (LAB) [18][19][20] and Bacillus spp. [21][22][23], express species-and strain-specific antifungal activity against different moulds.…”
Section: Introductionmentioning
confidence: 99%